(untitled) (Південний архів (історичні науки), 2022)
Purpose. The study of the period of defensive battles of the 6th and 12th armies in June – August 1941 is complicated by a limited number of available sources. In Soviet historical science, the outlined topic was under ideological prohibition. Therefore, the documents left after the destruction of the armies were kept in special funds of the Central Archive of the Ministry of Defense of the USSR in secrecy and were available only to students of the Military Academy named after M.V. Frunze, who had a military rank from lieutenant colonel and above, in order to study combat experience and subject to non-disclosure of military secrets. The article is devoted to the source analysis of the log of hostilities operations of the period of defensive battles of the 6th and 12th Soviet armies in the summer of 1941. Methods. The authors of log of hostilities actions and environment of their creation are foremost set. The date of creation of documents is also certain. During the internal critique of the source, the historical-critical method was used to compare the data of the logs of combat operations of the period of defensive battles of the 6th and 12th armies in the summer of 1941 with well-known facts. The origin of the documents that formed the basis for the creation of journals has been established. In addition, external criticism of sources was made. Results. In the course of our research, we found that the logbooks of the 6th and 12th Army headquarters were destroyed because of the German encirclement in the Zelena Brama tract near the village of Podvysokogo Kirovograd region. Today, researchers have access only to the journals of the Southern and Southwestern Fronts, as well as the 17th Rifle Corps, which until July 25, 1941 was part of the 12th Army. Conclusions. After analyzing the Soviet and modern literature on the history of defensive battles of the 6th and 12th armies at the initial stage of the German-Soviet war, we came to the conclusion that the logs of hostilities remained out of the attention of historians. The introduction of journals into scientific circulation makes it possible to make a broader analysis of the causes of death of two Soviet armies. Despite the fact that in the logs of hostilities the information is presented in a short version, their informative value lies in the fact that they can be used to establish the chronological sequence of events and the location of individual military clashes.